Analisis technology contribution coefficient (TCC) di UKM Gazal Makmur - Cahyuni Novia; Iqnatia Sundus Anisa; Ika Rafidah (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Technology is an important aspect for the success of an industry. Gazal Makmur UKM is an UKM that processes cassava into chips in Gazal Hamlet, Kotaanyar Village, Kotaanyar District, Probolinggo Regency. This study aims to calculate the value of the technology component contribution coefficient (TCC) and determine the priority of technology component development in Gazal Makmur SMEs. The method used in this study is the technometric method, namely the technology assessment method used to evaluate the contribution of technology components and the pairwise comparison matrix approach. The measured technology components include technoware (production equipment), humanware (human resource capabilities), infoware (information tools), and orgaware (organizational tools). The results of this study indicate that the contribution of the Orgaware component is the highest in Gazal Makmur SMEs (0.578), then humanware (0.467), humanware (0.252), and the smallest is technoware (0.0.244). The TCC value for Gazal Makmur SMEs is 0.418. The results of this calculation show that these SMEs have a TCC value below 0.7 and above 0.3, meaning that it can be concluded that these SMEs are classified as having a semi-modern level of technology with a reasonable technology category for the SME scale. Improving the quality of Gazal Makmur cassava chips SMEs starts from the orgaware component then humanware, infoware and finally orgaware.